Modelling academic dishonesty among undergraduates of Nigerian and Malaysian public universities - Moshood, Imran Adesile (Institute of Education, International Islamic University Malaysia, 2014)
This study examined the psychological factors underlying undergraduates' academic dishonesty, using the modified framework of the theory of planned behavior (TPB). The theory claimed that intentions to engage in a behavior are determined by three factors – attitudes toward behavior, perceived behavioral control, and subjective norms. The new variables introduced in the model were ethical judgment and cultural beliefs. Altogether, a total of 1800 students were involved. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and tests of convergence and discriminant validity were deployed to establish the psychometric properties of the seven-construct academic dishonesty model. The findings of the full-fledged structural model provided additional proofs about the utility of the TPB components to predict an array of behaviors. All the tested constructs except ethical judgment (ETJ) exerted a substantial statistically significant impact on intentions to engage in academic dishonesty. Intention too exerted a strong statistical significant influence on academic dishonesty. Although ETJ did not exert a substantial significant impact on intentions, it nonetheless had a direct considerable impact on actual academic dishonesty. Furthermore, cultural belief had a substantial direct influence on ethical judgment as well as indirect effect on actual academic dishonesty through the mediating role of ethical judgment. These results altogether suggested that students who exhibit a favorable disposition toward academic dishonesty, who operate in an environment with less restrictive norms against academic misconducts, and who have a high confidence in their ability to succeed in acts of academic dishonesty, all things being equal, will more likely form intention to engage and get involved eventually in actual academic dishonesty. A significant contribution of this study lied not only in its application of a social psychology's theoretical framework to investigate academic dishonesty; but its beaming the light of empirical investigation on gender and nationality invariant analyses of the seven-construct academic dishonesty model. It was evident in these analyses that the underlying psychological predictors of students' academic dishonesty were not moderated by gender or nationality affiliation of students. These findings implied that irrespective of gender and country of origin of undergraduates, the psychological factors shaping academic dishonesty were necessarily the same. That is, students' attitudes toward the conduct; the prevailing norms of the academic environment; the extent that students develop confidence in their own ability to cheat successfully; and level of their sense of ethical judgment. All these call for proactive actions from the faculty members, university administrators, education policy makers, parents, and even the students themselves.